Variable temperature effects of Open Top Chambers at polar and alpine sites explained by irradiance and snow depth - Stef Bokhorst; Ad Huiskes; Rien Aerts; Peter Convey; Elisabeth J. Cooper; Linda Dalen; Brigitta Erschbamer; Jón Gudmundsson; Annika Hofgaard; Robert D. Hollister; Jill Johnstone; Ingibjörg S. Jónsdóttir; et al. (Global Change Biology, 2013)
Environmental manipulation studies are integral to determining biological consequences of climate warming. Open Top Chambers ( OTC s) have been widely used to assess summer warming effects on terrestrial biota, with their effects during other seasons normally being given less attention even though chambers are often deployed year‐round. In addition, their effects on temperature extremes and freeze‐thaw events are poorly documented. To provide robust documentation of the microclimatic influences of OTC s throughout the year, we analysed temperature data from 20 studies distributed across polar and alpine regions. The effects of OTC s on mean temperature showed a large range (−0.9 to 2.1 °C) throughout the year, but did not differ significantly between studies. Increases in mean monthly and diurnal temperature were strongly related ( R 2 = 0.70) with irradiance, indicating that PAR can be used to predict the mean warming effect of OTC s. Deeper snow trapped in OTC s also induced higher temperatures at soil/vegetation level. OTC ‐induced changes in the frequency of freeze‐thaw events included an increase in autumn and decreases in spring and summer. Frequency of high‐temperature events in OTC s increased in spring, summer and autumn compared with non‐manipulated control plots. Frequency of low‐temperature events was reduced by deeper snow accumulation and higher mean temperatures. The strong interactions identified between aspects of ambient environmental conditions and effects of OTC s suggest that a detailed knowledge of snow depth, temperature and irradiance levels enables us to predict how OTC s will modify the microclimate at a particular site and season. Such predictive power allows a better mechanistic understanding of observed biotic response to experimental warming studies and for more informed design of future experiments. However, a need remains to quantify OTC effects on water availability and wind speed (affecting, for example, drying rates and water stress) in combination with microclimate measurements at organism level.